Synthesis, Spectral and Antimicrobial Studies of Some Oxomolybdenum(V) and Dioxomolybdenum(VI) Complexes of a Schiff Base Derived from 1-Phenyl- 2,3-dimethyl-4-amino-5-pyrazolone - HARIKUMARAN NAIR, M.L.; KUMARI NISHA, K.R. (Asian Journal of Chemistry, 2010)
Some novel oxomolybdenum(V) complexes of general formula [MoO(TAAP)XCl2] and dioxomolybdenum(VI) complexes of general formula [MoO2(TAAP)XCl] (X = Cl, NO3, NCS or ClO4 and TAAP-1-phenyl-2,3,-dimethyl-4-(N-thienylidene)-5-pyrazolone) have been synthesized and characterized by elemental analysis, IR, UV, ESR and NMR spectral studies. The thermal behaviour of the complex [MoO2(TAAP)NCSCl] has also been examined. The ligand and its few metal complexes were screened for their antibacterial activities against gram positive and gram negative bacteria and also screened for their antifungal activities. The molar conductance values of the complexes indicate that the complexes are non-electrolytes. The X-ray powder diffraction pattern of the complex [MoO2(TAAP)(NCS)Cl] has been examined and found to be orthorhombic with the unit cell dimensions such as a = 24.35 Å, b = 10.89 Å and c = 9.94 Å. The X-band ESR spectra indicate that the pentavalent Mo in the complexes [MoO(TAAP)Cl3], [MoO(TAAP)NCSCl2] and [MoO(TAAP)ClO4Cl2] is monomeric in nature.